Empowering Indigenous People Through Community-Based Economic Development Using Native Herbal Plants from Bukit Duabelas, Jambi - Ulfa, Maria; Muchlis, Fuad; Elwamendri; Kurniasih, Siti (LPPM Universitas Jambi, 2024)
This community service program aimed to empowering indigenous people through community-based economic development using native herbal plants from Bukit Duabelas, Jambi. A community-based social engineering approach was adopted, employing participatory methods such as group mentoring, focus group discussions (FGDs), and capacity-building training. The program was conducted from September to December 2022 in Pematang Kabau Village, Air Hitam Subdistrict, Sarolangun Regency. The main activities included: (1) assisting in the formation and formalization of indigenous people economic units, (2) ex-situ conservation through the cultivation of herbal plants outside the national park area, and (3) developing a marketing strategy for herbal products. The outcomes included the establishment of farmer groups, provision of tools for herbal processing, and the development of a nursery site for ex-situ conservation. These results are expected to serve as a foundational step toward fostering sustainable and inclusive economic independence for the SAD community living in and around Bukit Duabelas National Park.